TINJAUAN FIQHUL HADHOROH TERHADAP PENCEGAHAN LGBT: (Studi Kritis Terhadap Fenomena Upaya Kampanye LGBT di Media Sosial) - Choirur Rois; Ahmad Zainuri (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
Lesbians, Gays, Bisexuals, Transgender (LGBT) campaign efforts on various social media are getting more massive echoed by pro-LGBT groups. Openly through Instagram, Tiktok, etc., the LGBT community channel their creativity and expression to gain recognition and acceptance from netizens. Responding to this phenomenon, Indonesia as a Muslim-majority country in the elucidation of article 85 of the Family Resilience Bill defines LGBT as an act of sexual deviance. Jurisprudence as a science of law in Islam does not only talk about the halal and haram of a job. But behind the provisions of a law contains efforts to prevent deviations from the occurrence of human roles and functions based on their nature. This issue inspired the author to examine the construction of fiqh law as an effort to prevent and provide awareness to LGBT on social media. This study uses a sociological approach to Islamic law based on phenomenological and literature studies. The results of this study indicate: (1) Massive campaign efforts and LGBT hegemony in social media have a negative impact on the socio-cultural orientation of future generations. (2) Fiqhul hadhoroh in its legal construction has a conception that can be used as a solution in providing awareness and prevention of LGBT campaign efforts on social media (3) There is a spirit of collaboration between the concept of fiqhul hadhoroh and positive law in Indonesia in preventing and arousing LGBT campaign efforts in the media social.